Excluding Whom? Race, Gender, and Suspension in High School. Issue 4 (May 2022) - Erickson, Jacob H.; Pearson, Jennifer
Students of color are more apt to face exclusionary discipline in school, such as suspension or expulsion, than their white counterparts, and once suspended students may be more likely to drop out of school altogether. Utilizing the Education Longitudinal Study (ELS), we assess the separate and combined effects of various student level influences while controlling for contextual influences on the odds of suspension and dropping out. Results suggest students of color face a more punitive schooling experience and are more likely to experience scholastic exclusion even after controlling for a host of covaraites. Thus, findings indicate implicit perceptions of students of color, irrespective of their attitudes and behaviors, guide disciplinary practices which have real effects for students' subsequent academic experience.